Urbanization and structural transformation - Schmidt, Emily; Dorosh, Paul A.; Kedir Jemal, Mekamu; Smart, Jenny (International Food Policy Research Institute, 2020)
Chapter 12, “Urbanization and Structural Transformation,” describes patterns of urbanization in Ethiopia and government policy to promote development of secondary cities. Official population data indicate rapid urban growth, 4.2 percent per year between 1994 and 2015, far outpacing the overall population growth rate of 2.5 percent. By 2050 urbanization is expected to reach 38 percent with major implications for relative wage rates in rural versus urban areas, infrastructure needs, and public service delivery. Improved road infrastructure is improving connectivity across the country and promoting secondary city development. In addition, recent public investments to promote industrialization and increase manufacturing labor opportunities via newly constructed and planned industrial parks, though small relative to the overall economy, are designed to be a catalyst for future growth.